Workshop on climate-smart agriculture in Ashanti region, Ghana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
The video relates to the Ghana CCAFS Platform activity to profile Climate Smart Agriculture practices (CSA) to the region. The content deals with the Kumasi regional workshop to profile CSA practices in the Forest zone of Ghana.The first part of the video used a clip from CCAFS 2 degrees up to engage participants. The second covers the official opening session engaging political leaders (Regional Minister, Municipal Chief Executive, etc) The third part deals with technical presentation of technologies and practices in the zone by selected experts. The fourth part of the video captures group work of the participants to list, discuss and profile the practices according to given criteria.